Systematic review and meta-analysis of the association between maternal smoking in pregnancy and childhood overweight and obesity. - Rayfield, S; Plugge, E (BMJ Publishing Group, 2017)
Background By 2020 it is predicted that 60 million children worldwide will be overweight. Maternal smoking in pregnancy has been suggested as a contributing factor. Our objective was to systematically review studies on this, thereby expanding the evidence base for this association. Methods Systematic Review with meta-analysis, Prospero Registration number CRD42012002859. We searched Pubmed, Embase, Global Health, Web of Science and the Grey literature. We included prevalence, cohort and cross-sectional studies involving full term, singleton pregnancies. Published and unpublished studies through to 1st January 2015 in all languages, demonstrating an objective overweight outcome up until 18 years of age and data presented as an odds ratio were included. Quality assessment was undertaken using an adaption of the Newcastle-Ottawa scale. Statistical analysis performed using Review Manager Version 5·3. Findings The meta-analysis included 39 studies of 236, 687 children from Europe, Australia, North & South America and Asia. Maternal smoking in pregnancy ranged from 5·5-38·7%, with the prevalence of overweight from 6·3-32·1% and obesity from 2·6-17%. Pooled adjusted odds ratios demonstrated an elevated odds of maternal smoking in pregnancy for both childhood overweight (OR 1·37, 95% CI 1·28-1·46, I2 45%) and childhood obesity (OR 1·55, 95% CI 1·40-1·73, I2 24%). InterpretationFindings Our results demonstrate an association between maternal prenatal smoking and childhood overweight. This contributes to the growing evidence for the aetiology of childhood overweight, providing important information for policy makers and health professionals alike in planning cessation programmes or anti-smoking interventions for pregnant female smokers.